Professional Creativity as A Component of The Effective Activity of a Teacher - Abdula-Zade, Konstantin Zaurovich (2021)
The article considers the role and influence of professional creativity on the professional activities as an expression of the teacher’s creative abilities. The purpose of the article is a theoretical and empirical study of the influence of professional creativity on the effectiveness of a teacher’s professional activity. Attention is paid to the place and importance of creativity in the activities of a teacher. Based on an analysis of current literary sources, the phenomenon of professional creativity of a teacher is highlighted, a definition of this concept is given, and its structure and components are considered. The research methodology and its algorithm include a complex psychological and pedagogical experiment, diagnosing the stated parameters and statistical analysis of the results based on Spearman's rank correlation coefficient. The study of teachers’ creativity was carried out on the basis of the Institute of Foreign Languages of the Federal State Autonomous Educational Institution of Higher Education “The Peoples’ Friendship University of Russia” (RUDN) at the Center for Continuing Professional Education. For research purposes, an experimental and a control group were formed. Each group consisted of 35 teachers. The sample was homogeneous by age and gender. The results of the study allow us to conclude that there is a strong relationship between the professional creativity of a teacher and the effectiveness of the professional performance, which is confirmed by the results of statistical processing of the data obtained.